EQUIVALENCE BETWEEN ANTIMICROBIAL SUSCEPTIBILITY (in vitro) AND TREATMENT EFFICACY (in vivo) IN INFECTIOUS DISEASE PATIENTS TREATED WITH PIMENEM AND MERONEM IN THONG NHAT HOSPITAL AND GENERAL HOSPITAL PHU YEN PROVINCE - Nguyễn Đức, Công; Đỗ Kim, Quế; Hồ Sĩ, Dũng; Trần Gia, Huy; Hàn Đức, Đạt; Hà Phạm Trọng, Khang; Ngô Thế, Hoàng; Trần Thị Vân, Anh; Nguyễn Khánh, Vân; Lê , Hòa; Trương Quang Anh , Vũ; Trần Anh, Dũng; et al. (Journal of 175 Practical Medicine and Pharmacy, 2023)
Equivalence studies to compare the effect of generic meropenem with meropenem (brand name) have not been performed, especially comparing on the equivalent culture characteristics and antimicrobial susceptibility. Objectives: Equivalence comparison of antimicrobial susceptibility (in vitro) and treatment efficacy (in vivo) in infectious disease patients treated with Pimenem and Meronem (contents of 0.5g and 1g) at Thong Nhat Hospital and General hospital Phu Yen province. Methods: A controlled, multicenter clinical trial including 121 patients with community-acquired pneumonia, hospital-acquired pneumonia, sepsis, and biliary-abdominal infections from October 2019 to July 2022. There were 61 patients used Pimenem and 60 used Meronem similar in age, sex, pathological structure, severity based on APACHE II and SAPS II scores. Patients were diagnosed and assessed for the severity of the infection, taken microbiology specimens appropriately to cultures and made antibiogram, randomly treated with Pimenem or Meronem (0.5g or 1g based on indication), evaluated the effectiveness of treatment, from which analyzed the equivalence of meropenem antimicrobial susceptible. Results: The overall growth rate was 40.5%. Escherichia coli (14.0%), Kelbsiella pneumoniae (9.9%), Pseudomonas aeruginosa (8.3%) và Acinetobacter baumannii (6.6%). There was no significant differences in bacterial species between the Pimenem and Meronem groups (p=0.162). There was no significant difference in the proportion of bacteria sensitive and resistant to meropenem between the Pimenem group (86.4% and 9.1%) with Meronem group (66.7% and 18.5%) (p=0.268) as well as on average MIC (1,81±4,61 và 2,18±3,70, p=0,756). Analyzed on the subgroups 0.5g and 1g were also not statistically significant difference. The cured and improvement rate was 95.0%, which similar between Pimenem and Meronem in overall (95.1% and 95%, p=0.918), 0.5g subgroup (95.5 và 100%, p=0.583), 1g subgroup (94.9 và 91.9%, p=0.699). 92.8% of bacterial strains were not resistant to meropenem in the group that recovered while 100% were resistant to meropenem in the group of treatment failure (p<0,0001). Conclusions: The effectiveness of treatment was high and equivalent between the two groups Pimenem and Meronem (both 0.5g or 1g contents). There was no difference in the proportion of bacterial growth specimens, bacterial species, resistance to meropenem, or mean MIC value between Pimenem and Meronem groups in both 0.5g and 1g contents. Meropenem resistance was associated with treatment failure in both groups.